NATURE FRIENDLY TOURISM AND DEVELOPMENT OF TRAILER PARKS IN LATVIA - Grietiņa, Ilze; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
In order to further stimulate economic growth, the tourism sector needs to refocus its thinking by overputting the emphasis on generating profits on regional development. The establishment of trailer parks is a prerequisite for this. Kemper is an excellent means of movement that allows the ecological foot to be reduced, since it combines both the means of movement and the place of accommodation. Tourism without the use of an aircraft produces two times less CO2 emissions. Ecotourism meets the expectations of European travellers. They have important wilderness, rural areas, small towns. Latvia is a suitable place for the successful development of trailer parks, which will benefit not only the park business but also the surrounding entrepreneurs.